A rare case of prostate neuroendocrine tumor: A case report - Teh, Shunxing; Inn, Fam Xeng; Rizuana, Iqbal Hussain; WM, Wan Muhaizan (Frontiers in Oncology, 2022)
Small cell prostate neuroendocrine carcinoma (SCPC) is a rare, highly aggressive malignant tumour. We present a case of a 52-year-old Iranian man, presented with complaints of occasional gross haematuria and perineal pain for 6 months. PSA reading was 0.8 ng/ml. Digital rectal examination found a huge and hard prostate mass. He underwent transrectal ultrasound-guided (TRUS) biopsy of the prostate. Histopathology result showed high grade small cell neuroendocrine carcinoma. Immunohistochemical markers were positive for Synaptophysin with a Ki67 index of almost 100%. However, CD 56 and Chromogranin A markers were negative. Magnetic resonance imaging (MRI) of the prostate showed prostate mass with invasion to the rectum; while contrast enhanced computed tomography of the thorax, abdomen and pelvis(CT TAP) ruled out metastasis. A multidisciplinary team discussion was carried out and decision was made for concurrent radiation and chemotherapy. There is a lack of consensus on the management of SCPC. The main modality of management is concurrent radiation and chemotherapy in view of the majority of cases presented in late stages. It is highly aggressive, with poor responses to hormonal therapy and carries a poor prognosis.